Analysis of morphological and neurochemical changes in subthalamic nucleus neurons in response to a unilateral 6-OHDA lesion of the substantia nigra in adult rats - Katayoun Sedaghat; Andrew L. Gundlach; David I. Finkelstein (IBRO Neuroscience Reports, 2021)
Background: Subthalamic nucleus (STN) neurons undergo changes in their pattern of activity and morphology during the clinical course of Parkinson’s disease (PD). Striatal dopamine depletion and hyperactivity of neurons in the parafascicular nucleus (Pf) of the intralaminar thalamus are predicted to contribute to the STN changes. Objective: This study investigated possible morphological and neurochemical changes in STN neurons in a rat model of unilateral, nigral dopamine neuron loss, in relation to previously documented alterations in Pf neurons. Methods: Male Sprague-Dawley rats received a unilateral injection of 6-hydroxydopamine (6-OHDA) into the substantia nigra pars compacta (SNpc). Rats were randomly divided into two groups (6/group) for study at 1 and 5 months by post-treatment. The extent of SNpc dopamine neuron damage was assessed in an amphetamine-induced rotation test and postmortem assessment of tyrosine hydroxylase mRNA levels using in situ hybridization histochemistry. Neural cross-sectional measurements and assessment of vesicular glutamate transporter-2 (vGlut2) mRNA levels were performed to measure the impact on neurons in the STN. Results: A unilateral SNpc dopaminergic neuron lesion significantly decreased the cross-sectional area of STN neurons ipsilateral to the lesion, at 1 month (P < 0.05) and 5 months (P < 0.01) post-lesion, while bilateral vGlut2 mRNA levels in STN neurons were unaltered. Conclusions: Decreased size of STN neurons in the presence of sustained vGlut2 mRNA levels following a unilateral SNpc 6-OHDA lesion, indicate altered STN physiology. This study presents further details of changes within the STN, coincident with observed alterations in Pf neurons and behaviour. Data availability: The data associated with the findings of this study are available from the corresponding author upon request.